CARIMBÓ – A Flexible Framework Proposal for the Return Path in Brazilian Digital Television - Coutinho, Fernando Koch Mauro Margalho; Francês, Carlos Renato Lisboa; Costa, João Crisóstomo W. A. (INFOCOMP Journal of Computer Science, 2005)
This paper proposes a framework to the return path on the Brazilian digital television. It presents an alternative way to achieve user based interactivity by utilizing the existing Wireless Distribution System resource (WDS) The utilization of this resource in areas with no infrastructure of telecommunications, like the Amazonian region, creates a perspective of integration for the native people to the digital inclusion programs organized by federal government. In order to evaluate the feasibility of this proposal the Network Simulator (NS) was used.